(untitled) (Academia Journal of Medicine, 2024)
This study aimed to ascertain the prevalence of cysts and tumors among patients attending a dental college. Utilizing retrospective data analysis, a significant sample size was examined. Findings reveal critical insights into occurrence rates, contributing to improved diagnostic and therapeutic strategies within the dental community.